Imagining a new public space in the foreshore by re-creating the city-sea relationship - Watson-Smith, Adam Graham (School of Architecture, Planning and Geomatics, 2017)
Aim: Reconnect the City to the Sea through investment in the pedestrian and public space, supported by activity generating and accommodating architecture. Theory question: What architectural methods are being employed in global port-side cities to reinvent and make use of large tracts of de-valued inner city land? Technology question: What is the nature of the physical condition that the foreshore area presents and what impact has this had on the haphazard development of this inner city space? Sub Questions: What are the key factors in global cities' development and fabric which have resulted in large inner city tracts of undervalued land, and their condition? What are the implications of different modes of mobility within urban space, and particularly their effects on the resulting urban form, and utilization of this space? What negative effects of mobility in a global society are universal to all contemporary cities and societies, and what are some of the contextually derived typological solutions? What are the primary opportunities and technical challenges presented by the unique conditions of the foreshore to development?